Optimalisasi Kandungan Al-Qur’an Dalam Menghadapi Wabah Penyakit - Ma'ruf, Annas (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This article is the result of research based on the current reality regarding the handling of disease outbreaks, and linking it to the verses of the Qur'an. In the Qur'an, disease outbreaks are mentioned several times, which shows the potential for science that can be explored to be applied in the present era. Since early 2019, the world has been hit by a major outbreak caused by a small creature called a virus. Coronavirus Disease (COVID-19) has become a major threat that has an impact on life without discrimination; anyone is at risk of contracting this infectious disease. The COVID-19 outbreak was first detected in Wuhan City, China, at the end of 2019 and has spread to almost 200 countries around the world, including Indonesia. The Qur'an is a source of knowledge that contains various aspects of life, such as history, health, and exemplary behavior. Methods for dealing with various problems can also be taken from the information contained in the Qur'an. Therefore, as Muslims, we have an obligation to explore and understand how the knowledge contained in the Qur'an can be implemented in the current context.